Tata Bahasa Kasus (Case Grammar) - Suparnis Suparnis (Fakultas Bahasa dan Seni UNP, 2008)
Case grammar was first introduced by Charles J. Fillmore. It is a modification of the theory of grammar transformation which previously presents the conceptual framework of case relationship with the traditional grammar. Fillmore develops grammatical case after the problem of grammatical generative transformation occurred. He views the existence of semantic role on nominal in relationship with the verb which is not explained by grammatical generative transformation Keywords: case grammar, grammatical, generative transformation